Urban Household Demand for Fresh Fruits and Vegetables in Thailand - Lippe, Rattiya Suddeephong; Seebens, Holger; Isvilanonda, Somporn (Asian Journal of Applied Economics, 2013)
บทคัดย่อ ระบบสินค้าอาหารเปลี่ยนแปลงไปอย่างรวดเร็วในประเทศกำลังพัฒนา โดยเฉพาะอย่างยิ่งในด้านคุณภาพและความปลอดภัยของอาหารสด การเข้าใจรูปแบบอุปสงค์การบริโภคและปัจจัยแฝงนับเป็นองค์ความรู้สำคัญที่จะช่วยกำหนดนโยบายอาหาร และเป็นข้อมูลสำคัญต่อผู้ผลิตและผู้จำหน่ายในประเทศ การศึกษาครั้งนี้ประมาณค่าสัมประสิทธิ์ของอุปสงค์การบริโภคผักและผลไม้สด จำแนกตามคุณลักษณะของผลผลิตและกระบวนการผลิต โดยใช้กรอบแนวคิดการจัดสรรงบประมาณแบบสองขั้นตอน การวิเคราะห์อาศัยข้อมูลสำรวจครัวเรือนในกรุงเทพฯ และเขตเมืองจังหวัดเชียงใหม่ 300 และ 200 ครัวเรือน ตามลำดับในช่วง พ.ศ. 2550 แนวโน้มการบริโภคผักและผลไม้สดในเขตเมืองเน้นคุณภาพ ความปลอดภัย และความสะดวกสบายในการบริโภคมากขึ้น แนวโน้มนี้สอดคล้องกับฐานะทางเศรษฐกิจและรายได้ของครัวเรือน ตลอดจนระดับการศึกษาของผู้บริโภคที่สูงขึ้น ปริมาณการบริโภคผักและผลไม้สดที่มาจากโซ่อุปทานสมัยใหม่ของครัวเรือนมีการตอบสนองต่อราคาค่อนข้างสูง ภาคส่วนที่เกี่ยวข้องควรปรับตัวต่อการเปลี่ยนแปลงความพึงพอใจของผู้บริโภค ร้านค้าปลีกแบบดั้งเดิมควรสร้างความเชื่อมั่นให้กับผู้บริโภคโดยสร้างมาตรฐานคุณภาพและความปลอดภัยของผลผลิต ร้านค้าปลีกสมัยใหม่ควรรักษามาตรฐานที่มีอยู่และเพิ่มประสิทธิภาพการผลิตโดยนำมาตรฐานขั้นสูงมาปรับใช้ นโยบายและโครงการต่างๆ ที่ช่วยเพิ่มรายได้และระดับการศึกษาของครัวเรือน จะไปกระตุ้นการบริโภคสินค้าที่มีคุณภาพและเพิ่มความหลากหลายในการบริโภค รัฐควรสนับสนุนการพัฒนาและการใช้มาตรฐานที่น่าเชื่อถือ รวมถึงระบบการรับรองผลิตภัณฑ์และกระบวนการผลิต การรณรงค์ให้ข้อมูลแก่ผู้บริโภคเรื่องอาหารคุณภาพและปลอดภัยจะช่วยขยายตลาดสินค้ากลุ่มดังกล่าว และจะเอื้อประโยชน์ต่อเกษตรกรผู้ผลิตต่อไป คำสำคัญ : ผลไม้, ผัก, ความยืดหยุ่นของอุปสงค์, อาหารปลอดภัย, ระบบสมการอุปสงค์ Abstract Food systems are undergoing profound changes in developing countries, particularly on fresh produce with specific quality and safety attributes. An understanding of the demandpatterns and their underlying determinants are important in designing food policies and generating information for local supply actors. The disaggregate demand parameters for fresh fruits & vegetables that have different product and process attributes were estimated by using the two-stage budgeting framework. The methodology accounted for censored data. The analysis is based on crosssectional data of 300 households in Bangkok and 200 households in urban areas of Chiang Mai in 2007. The trend in domestic demand for fresh fruits & vegetables is towards an emphasis on safety, quality and convenience. Economic development, along with higher household incomes and educational levels of consumers, contribute to this tendency. Households are becoming more price responsive to fresh produce from modern supply chain sectors. The entire food sector should adapt to changes in consumers’ preferences. Traditional retailers should create customer trust by adopting safety and quality standards and upgrading the quality attributes of fresh produce. Modern retailers should sustain own reputation and improve product lines by adopting premium standards. Policies and programs that foster income growth along with better education will spur demand for better quality products and lead to diversification in diets. The government should encourage the development and adoption of credible standards and product and process certification schemes. An information campaign to educate consumers on food safety and quality would expand the market for fresh produce and benefit farmers. Keywords : fruit, vegetable, demand elasticity, food safety, almost ideal demand system